Mechanistic Study of CO Titration on CuxO/Cu(1 1 1) (x≤2) Surfaces. Issue 8 (26th June 2014) - An, Wei; Baber, Ashleigh E.; Xu, Fang; Soldemo, Markus; Weissenrieder, Jonas; Stacchiola, Dario; Liu, Ping
Abstract The reducibility of metal oxides is of great importance to their catalytic behavior. Herein, we combined ambient‐pressure scanning tunneling microscopy (AP–STM), X‐ray photoemission spectroscopy (AP–XPS), and DFT calculations to study the CO titration of CuxO thin films supported on Cu(1 1 1) (CuxO/Cu(1 1 1)) aiming to gain a better understanding of the roles that the Cu(1 1 1) support and surface defects play in tuning catalytic performances. Different conformations have been observed during the reduction, namely, the 44 structure and a recently identified (5–7–7–5) Stone–Wales defects (5–7 structure). The DFT calculations revealed that the Cu(1 1 1) support is important to the reducibility of supported CuxO thin films. Compared with the case for the Cu2O(1 1 1) bulk surface, at the initial stage CO titration is less favorable on both the 44 and 5–7 structures. The strong CuxO↔Cu interaction accompanied with the charge transfer from Cu to CuxO is able to stabilize the oxide film and hinder the removal of O. However, with the formation of more oxygen vacancies, the binding between CuxO and Cu(1 1 1) is weakened and the oxide film is destabilized, and Cu2O(1 1 1) is likely to become the most stable system under the reaction conditions. In addition, the surface defects also play an essential role. With the proceeding of the CO titration reaction, the 5–7 structure displays the highest activity among all three systems. Stone–Wales defects on the surface of the 5–7 structure exhibit a large difference from the 44 structure and Cu2O(1 1 1) in CO binding energy, stability of lattice oxygen, and, therefore, the reduction activity. The DFT results agree well with the experimental measurements, demonstrating that by adopting the unique conformation, the 5–7 structure is the active phase of CuxO, which is able to facilitate the redox reaction and the Cu2O/Cu(1 1 1)↔Cu transition.